Implementasi Metode Full Costing untuk Menentukan Harga Jual Produk - Ribangun Bamban Jakaria; Herlyana Putra Azizul Hakim; Muhammad Rizal Syaifudin; Moch Efendi Kurniawan (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2024)
Determining selling prices is one of the important and crucial problems that many small and medium companies experience. This is due to the large production price of the product (HPP), which is caused by many expenditure items not being identified, or the selling price having been set while the HPP is not yet known. This research aims to determine the amount of costs incurred by the company, in order to make it easier for the company to find out the amount of HPP. The method used is the full costing method, which is a method used to avoid losses resulting from product sales so that the company minimizes the price of making the product. The results of this research show that the HPP amount is 962,966,450 rupiah per year by adding 10-20% margin value so that the selling price of fertilizer is 2,650 thousand per kilogram of fertilizer.